Roadmap for operational sustainability: an approach based on Integrated Management Systems and Business Process Management - Ferreira, Camila dos Santos; Poltronieri, Camila Fabricio; Iritani, Diego Rodrigues; Vicente, Mônica Tani; de Nadai, Stefano; Ometto, Aldo Roberto; Gerolamo, Mateus Cecílio; Carpinetti, Luiz Cesar Ribeiro (Revista Gestão da Produção Operações e Sistemas, 2021)
Purpose - This paper proposes a roadmap for the sustainability of operations based on the principles and practices taken from Integrated Management Systems (IMS) and Business Process Management (BPM). Theoretical framework - Companies must consider results based on the economic, social, and environmental dimensions of the Triple Bottom Line, and as such, some researchers point to the contribution made by IMS for sustainability. Another important aspect of changing to more sustainable business models is organizational structure. BPM focuses on implementing horizontal management in the organization through business processes. Design/methodology/approach – Within this context, a Systematic Literature Review (SLR) was carried out to identify IMS and BPM principles, practices and techniques, then a roadmap was designed and field research was carried out by specialists. Findings - Field research findings indicate that the roadmap represents a framework which can support organizations to achieve their sustainability goals. Research limitations/implications - One of the limitations in the study was the reduced number of specialists who analyzed the roadmap. Therefore, it is suggested, as a further study, that this roadmap is validated by other experts, including people from other countries. Another limitation is that the study must progress further on the issues of implementation posed by the proposed roadmap. As such, a further study should be carried out to address this point. Originality/value - This study uses concepts that have already been consolidated in the literature (IMS and BPM) as support for companies that seek to become more sustainable. Key words - Integrated Management System; Business Process Management; Roadmap; Sustainability; IMS; BPM.